Synthesis of Schiff Bases of Benzaldehyde and Salicylaldehyde as Anti-inflammatory Agents - Tagreed N. Omar (College of Pharmacy University of Baghdad, 2017)
Three Schiff bases from Benzaldehyde and Salicylaldehyde have been synthesized (A, 1and 2) and two of them (1and 2) have been tested for anti-inflammatory activity. The p-aminobenzene sulfonamide has been synthesized from acetanilide through the addition of excess chlorosulfonic acid then concentrated ammonia solution; Schiff base of this derivative (2) exhibited good level of activity against egg-white induced edema in rat hind paw, while the other tested derivative exhibited no activity. Key words: Schiff bases, sulfonamide derivatives, salicylaldehyde